Avicenna on the Opposition of Conditional Proposition - Yusuf Daşdemir (Felsefe Dünyası)
This paper examines Avicenna's remarks and consideretions on conditional propositions and the oppositional relations between them. İt also tries to detect his ancient and Arabic logic after him. İt aims to show that Avicenna's theory of conditionals has original aspects different from that of ancient logicans and that the improved this theory significantly. İt also aim at showing that Avicenna's theory is essentially Peripatetic, not Stoic.